Tailored nurse-led cardiac rehabilitation after myocardial infarction results in better risk factor control at one year compared to traditional care: a retrospective observational study - Ögmundsdottir Michelsen, Halldora; Nilsson, Marie; Scherstén, Fredrik; Sjölin, Ingela; Schiopu, Alexandru; Leosdottir, Margret (BMC cardiovascular disorders, 2018)
Background Cardiac rehabilitation improves prognosis after an acute myocardial infarction (AMI), however, the optimal method of implementation is unknown. The aim of the study was to evaluate the effect of individually-tailored, nurse-led cardiac rehabilitation on patient outcomes. Method This single-centre retrospective observational study included 217 patients (62 ± 9 years, 73% men). All patients attended cardiac rehabilitation including at least two follow-up consultations with a nurse. Patients receiving traditional care ( n = 105) had a routine cardiologist consultation, while for those receiving tailored care ( n = 112) their need for a cardiologist consultation was individually evaluated by the nurses. Regression analysis was used to analyse risk factor control and hospital readmissions at one year. Results Patients in the tailored group achieved better control of total cholesterol (− 0.1 vs + 0.4 mmol/L change between baseline (time of index event) and 12–14-month follow-up, ( p = 0.01), LDL cholesterol (− 0.1 vs + 0.2 mmol/L, p = 0.02) and systolic blood pressure (− 2.1 vs + 4.3 mmHg, p = 0.01). Active smokers, at baseline, were more often smoke-free at one-year in the tailored group [OR 0.32 (0.1–1.0), p = 0.05]. There was a no significant difference in re-admissions during the first year of follow-up. In the tailored group 60% of the patients had a cardiologist consultation compared to 98% in the traditional group ( p < 0.001). The number of nurse visits was the same in both groups, while the number of telephone contacts was 38% higher in the tailored group ( p = 0.02). Conclusion A tailored, nurse-led cardiac rehabilitation programme can improve risk factor management in post-AMI patients.